ARTIFICIAL INTELLIGENCE -DRIVEN COMPUTATIONAL SOCIAL NETWORKS IN DRIVING SUSTAINABLE E-COMMERCE IN THE ERA OF INFORMATION TECHNOLOGY - Dr. Kiran Sharma; Dr. Sana Zaidi; Dr. Pallavi Bhardwaj (International Educational Journal of Science and Engineering, 2025)
The objective of this study is to examine the mediating role of environmental consciousness in the relationship between AI-driven computational social networks, information technology infrastructure, and sustainable e-commerce performance. To achieve this, an online survey was administered to 250 participants, and the collected data underwent structural equation modeling analysis. It is suggested that a good model should have an SRMR value below 0.08, and in this study, the SRMR value was 0.05, indicating an acceptable level of structural model fitness. The results demonstrate the significant influence of both AI-driven computational social networks and information technology infrastructure on sustainable e-commerce performance. Furthermore, the findings indicate that environmental consciousness partially mediates the connection between AI-driven computational social networks, information technology infrastructure, and sustainable e-commerce performance. By considering the partial moderating effect of environmental consciousness, it will shed light on the complex dynamics at play. The findings will offer valuable insights for businesses aiming to leverage AI-driven computational social networks and information technology infrastructure to enhance their sustainable e-commerce practices and performance.